2005
DOI: 10.1093/qjmed/hci113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an adult Duchenne muscular dystrophy population

Abstract: Adult patients with DMD develop progressive impairment, due to respiratory, orthopaedic and general medical factors. However, the particular areas of difficulty in this study often reflected inadequate and poorly directed social and medical support, illustrating the need for improvements in the structure, co-ordination and breadth of rehabilitation services for adult patients with DMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 32 publications
5
53
0
2
Order By: Relevance
“…[R3] 9 But on its own, all of the men said that the conversation had been limited and overly medicalised and they did not view these exchanges as tantamount to a conversation about end of life. Conversations about resuscitation were regarded as important for the reasons stated above but only a small part of the picture.…”
Section: What End Of Life Conversations Have Men Had?mentioning
confidence: 99%
See 1 more Smart Citation
“…[R3] 9 But on its own, all of the men said that the conversation had been limited and overly medicalised and they did not view these exchanges as tantamount to a conversation about end of life. Conversations about resuscitation were regarded as important for the reasons stated above but only a small part of the picture.…”
Section: What End Of Life Conversations Have Men Had?mentioning
confidence: 99%
“…5 The literature around end of life care in neuromuscular disorders (NMD) is not extensive. In one retrospective case note review of 24 men and one symptomatic female carrier referred to an adult neuromuscular clinic over a 7-year period, nine patients died during the observation period [9]. The paper noted that 'patients and their families were aware of disease progression and usually understood the natural history of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…The average age at death is around 19 years (Bushby et al, 2010), although life expectancy is extending with improved healthcare practices (Abbott & Carpenter, 2009). However, the continual loss of mobility and function leads to serious health problems including respiratory and cardiac deterioration, and curvature of the spine (scoliosis), which is treated with spinal surgery (Parker et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…35 patients from the cohort are still alive (aged 22-31 years); 18 died (aged [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Patients were ventilated by NIV (29/53) or IV (33/53).…”
Section: Causes Of Death and Ages Of Survival In Dmd What Is The Carmentioning
confidence: 99%
“…With the increase in age, many of them experience gastrointestinal symptoms which several studies have confirmed [12,[27][28][29][30].…”
Section: Gastrointestinal Problems In Dmdmentioning
confidence: 99%